Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1136/bmjopen-2017-016288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Maternity Units: a prospective cohort study of freestanding midwife-led primary maternity units in New Zealand—clinical outcomes

Abstract: ObjectiveTo compare maternal and neonatal birth outcomes and morbidities associated with the intention to give birth in a freestanding primary level midwife-led maternity unit (PMU) or tertiary level obstetric-led maternity hospital (TMH) in Canterbury, Aotearoa/New Zealand.DesignProspective cohort study.Participants407 women who intended to give birth in a PMU and 285 women who intended to give birth at the TMH in 2010–2011. All of the women planning a TMH birth were ‘low risk’, and 29 of the PMU cohort had i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
0
34
0
2
Order By: Relevance
“…The intrapartum and immediate postpartum (within 12 hours of birth) transfer rate was 9.3% (n=104), lower than the 19% (n=6002), 21.9% (n=2,468) and 17.3% (n=70) reported by Bailey (2017), Hollowell et al (2011) and Grigg et al (2017), respectively. However, these studies either included maternal and neonatal transfers up to 48 hours (Grigg et al, 2017) or did not define the timeframe (Bailey, 2017;Hollowell et al, 2011). Sixty-nine percent of the transfers were primigravid women.…”
Section: Rates Of Transfermentioning
confidence: 63%
See 1 more Smart Citation
“…The intrapartum and immediate postpartum (within 12 hours of birth) transfer rate was 9.3% (n=104), lower than the 19% (n=6002), 21.9% (n=2,468) and 17.3% (n=70) reported by Bailey (2017), Hollowell et al (2011) and Grigg et al (2017), respectively. However, these studies either included maternal and neonatal transfers up to 48 hours (Grigg et al, 2017) or did not define the timeframe (Bailey, 2017;Hollowell et al, 2011). Sixty-nine percent of the transfers were primigravid women.…”
Section: Rates Of Transfermentioning
confidence: 63%
“…Further prospective, retrospective and population based studies from Denmark (Overgaard, Møller, Fenger-Grøn, Knudsen, & Sandall, 2011), the Netherlands (Wiegerinck et al, 2015), Australia (Homer et al, 2014;Laws, Tracy, & Sullivan, 2010;Monk, Tracy, Foureur, Grigg, & Tracy, 2014), United States of America (Stapleton, Osborne, & Illuzzi, 2013) and NZ (Bailey, 2017;Davis et al, 2011;Grigg et al, 2017) reported significantly fewer obstetric interventions (such as instrumental birth, emergency caesarean section, labour augmentation, episiotomy) for mothers and no difference in neonatal mortality and morbidity for babies, when choosing midwifery-led settings (home and PMU) over obstetric-led hospitals. In contrast, population-based studies from the USA report higher neonatal mortality for babies born at home (Grünebaum et al, 2014;Wax et al, 2010) and a higher prevalence of Apgars of 0 at 5-min and neurological dysfunction in babies born at home or at a PMU (Grünebaum et al, 2014) compared to births at a TMH.…”
Section: Introductionmentioning
confidence: 99%
“…newborn care was performed by obstetric nurse or obstetrician and hospital units that had the presence of physician (11) . Regarding the prevalence of Apgar score < 7 at the fifth minute, the international literature shows lower prevalences, but with no significant differences for care in Normal Birth Center, when compared with the care for low-risk women in the hospital (12)(13)(14)(15) . However, the prevalences are higher than in the present study.…”
Section: Factors Associated With Low Apgar In Newborns In Birth Centermentioning
confidence: 95%
“…However, the prevalences are higher than in the present study. In extra-hospital NDC in Australia and New Zealand, the prevalence was 1.2% and 2%, respectively (12)(13) . In Denmark, the prevalence of Apgar score < 7 at the first minute is below 2.5% (14) .…”
Section: Factors Associated With Low Apgar In Newborns In Birth Centermentioning
confidence: 96%
“…Compared to standard obstetric care, advantages of midwife-led models of care (MLC) have been reported, including an increased vaginal birth rate with less interventions, and a shorter duration of labor (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). MLCs comprise a spectrum of care which include home births (HB), births in freestanding midwifery units (FMU), and alongside midwifery units (AMU).…”
Section: Introductionmentioning
confidence: 99%